How comprehensive are research studies investigating the efficacy of technology‐enhanced learning resources in anatomy education? A systematic review. Issue 3 (13th December 2017) - Clunie, Lauren; Morris, Neil P.; Joynes, Viktoria C.T.; Pickering, James D.
Abstract : Anatomy education is at the forefront of integrating innovative technologies into its curricula. However, despite this rise in technology numerous authors have commented on the shortfall in efficacy studies to assess the impact such technology‐enhanced learning (TEL) resources have on learning. To assess the range of evaluation approaches to TEL across anatomy education, a systematic review was conducted using MEDLINE, the Educational Resources Information Centre (ERIC), Scopus, and Google Scholar, with a total of 3, 345 articles retrieved. Following the PRISMA method for reporting items, 153 articles were identified and reviewed against a published framework—the technology‐enhanced learning evaluation model (TELEM). The model allowed published reports to be categorized according to evaluations at the level of (1) learner satisfaction, (2) learning gain, (3) learner impact, and (4) institutional impact. The results of this systematic review reveal that most evaluation studies into TEL within anatomy curricula were based on learner satisfaction, followed by module or course learning outcomes. Randomized controlled studies assessing learning gain with a specific TEL resource were in a minority, with no studies reporting a comprehensive assessment on the overall impact of introducing a specific TEL resource (e.g., return on investment). This systematic review has provided clear evidence that anatomy education is engaged in evaluating the impact of TEL resources on student education, although it remains at a level that fails to provide comprehensive causative evidence. Anat Sci Educ 11: 303–319. © 2017 American Association of Anatomists.